The Prophetic Approach in Increasing Religious Concepts among Primary School Students through Educational Activities - Al-sawalgah, Luba Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the prophetic approach and its effect on increasing religious concepts in the subject of education, (the number of its students reached (40) students from the fifth basic class students in my school (a student and a preliminary school for students) (20 students), and this study indicated a methodology Semi-experimental research, and two groups were chosen from the experimental group and taught through educational activities for the concepts of Islamic education and the controlled curriculum, and they were taught according to the usual method, by 20 students per group.The results of the study were effective for students who were taught according to scientific activities and modern methods. It was found that there were statistically significant differences (α=0, 05) in learning skills in scientific activities at the basic stage for sixth-graders in basic science to learn in the usual way, it was in the interest of the group that learned about the scientific activities, and in light of the results, the study recommended that scientific activities should be activated according to modern methods, especially in the science subject in Zarqa Governorate. The study also recommended a training contract for male and female teachers in order to develop learning skills through activities.
Keywords: learning by activities; scientific activities; skills